Association of biomarkers of inflammation with hospitalization for heart failure and death in patients with atrial fibrillation. (25th November 2020) - Benz, A.P; Aeschbacher, S; Krisai, P; Blum, S; Meyre, P; Blum, M.R; Rodondi, N; Di Valentino, M; Kobza, R; De Perna, M.L; Bonati, L.H; Beer, J.H; et al.
Abstract: Background: Hospitalization for heart failure and death are among the most common adverse clinical outcomes in patients with atrial fibrillation (AF). The underlying mechanisms are poorly understood. Purpose: We hypothesised that inflammation, quantified by plasma levels of C-reactive protein (CRP) and interleukin 6 (IL-6), is independently associated with hospitalization for heart failure and death in a large, contemporary cohort of AF patients. Methods: Patients with established AF and 65 years of age or older were enrolled in two large, prospective, multicentre cohort studies in Switzerland. Plasma levels of high-sensitivity (hs) CRP and IL-6 were measured from frozen EDTA plasma samples obtained at baseline. Using these two biomarkers, we calculated an inflammation score ranging from 0 to 4 (1 point for each biomarker between the 50th and 75th percentile, 2 points for each biomarker above the 75th percentile). We constructed multivariable Cox proportional hazards models to quantify the associations of hs-CRP, IL-6 and the inflammation score with time to first hospitalization for heart failure and time to all-cause mortality, respectively. Results: A total of 3, 784 patients with AF (median age 72 years, 28% women, 24% with a prior history of heart failure and 84% anticoagulation use at baseline) were followed for a median (interquartile range [IQR]) of 4.0 (2.9–5.1) years. The median (IQR) plasma levels of hs-CRP and IL-6 at baseline were 1.64 (0.81–3.69) mg/L and 3.42 (2.14–5.60) pg/mL, respectively. The incidence rates of hospitalization for heart failure and death were 3.04 and 2.80 per 100 person-years, respectively. After multivariable adjustment, both biomarkers were significantly associated with the risk of hospitalization for heart failure (per increase in 1 standard deviation [SD], adjusted hazard ratio [aHR] 1.22, 95% confidence interval [CI] 1.11–1.34 for log-transformed hs-CRP, and aHR 1.48, 95% CI 1.35–1.62 for log-transformed IL-6) and death (per increase in 1 SD, aHR 1.40, 95% CI 1.27–1.54 for log-transformed hs-CRP, and aHR 1.67, 95% CI 1.53–1.81 for log-transformed IL-6). Incidence rates of hospitalization for heart failure increased from 1.34 to 7.31 per 100 person-years across categories of the inflammation score (Figure 1). A strong relationship persisted after multivariable adjustment. Similar findings were observed for all-cause mortality. Conclusions: Inflammation is a strong predictor of hospitalization for heart failure and death in patients with AF. Targeting inflammation may be a promising treatment strategy to improve outcomes in these patients at high risk for adverse outcomes. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Swiss National Science Foundation